Mixed layer depth values for the n = 1968 modern dinocyst database extracted from the monthly climatology by Holte et al. (2017) - Wu, Xiner (In: Wu, X (2025): Mixed layer depth values for the n = 1968 modern dinocyst database [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982265, 2025)
Monthly, seasonal and annual mixed layer depth (MLD) values at the 1968 sites of the modern dinocyst database by de Vernal et al. (2020). The MLD values were extracted from the monthly climatology based on Argo profiles of 2000-2021 by Holte et al. (2017). MLD values corresponding to each of the the previously published 1968 sites were determined with a density algorithm.
Keywords: Dinocyst database; mixed-layer depth; Northern Hemisphere; Paleoceanographic proxies